Promoting learners’ autonomy by using Facebook to enhance students’ writing skills / Syazliyati Ibrahim, Sharina Saad, Norlizawati Md Tahir and Phaveena Primsuwan - Ibrahim, Syazliyati; Saad, Sharina; Md Tahir, Norlizawati; Primsuwan, Phaveena (Universiti Teknologi MARA Cawangan Kedah, 2018)
Language learning in the 21st century develops in tandem with technology. The growth of social media as the platform for communication is a positive element that can influence students’ learning especially in languages. One clear advantage of having such media is that students can be autonomous in their learning because they are already familiar with the platform and they use these sites in their daily lives. VELLP or Virtual English Language Learning Programme is one such agenda that has managed to take advantage of the popular usage of social media amongst students today. This programme is created to cater to thirty students of SMK Bakar Arang, Sungai Petani who have the potential to become better English language users. All thirty students are invited to join the online learning community in Facebook, moderated by four English language lecturers. Diverse topics and interesting issues were raised in the online forum, enabling the students to communicate with one another using correct language. A pretest and a posttest were given; and data from the tests were tabulated to show the effectiveness of the programme. All in all, VELLP has managed to prove that an online chatroom or an online community is able to facilitate second language learners to practice their writing skills in the target language in a fun and relaxed manner.